Symptoms of Delik Report Conflict of Name Pollution on Social Network Media - E. Solihatin; Sukirmiyad; K. N. Denhas (Future Science)
Misunderstandings in the communication process often occur because the parties do not understand each other's text and context in the speech delivered. This misunderstanding eventually led to conflict which led to reporting to the police on the basis of defamation. Defamation continues to increase as information and communication technology advances, namely through social media. The purpose of this study is to describe the symptoms of conflict through complaints of defamation on social networking media. The research method used is descriptive qualitative. Data collection is done through observation, in-depth interviews, and documentation. Research location in East Java Regional Police. Checking the validity of the data is used the data source triangulation technique. The unit of analysis is individuals. The data analysis of this study used the interactive model of qualitative data analysis techniques of Miles and Huberman. The results of this study are the symptoms of conflict reports of complaints of defamation complaints on social networking media, namely intrapersonal conflict caused by (a) weak communication because they do not understand the text and language context delivered; (b) There is hostility or envy between individuals or groups; and (c) The existence of friction between individuals in communication.